Struktur Anatomi Akar, Batang dan Daun Jabon Putih (Anthocephalus cadamba (Roxb.) Miq) yang Mengalami Cekaman Kekeringan dan Genangan - Riza Linda, Janur Prahtiwi Ninilouw, Mukarlina, (Jurnal Protobiont, 2015)
White Jabon (Anthocephalus cadamba) plant is a kind of tree has a high prospect for the industry forest and reboisation plant in Indonesia. The jabon plant growing is very influenced by sufficient water evaluable so it can influences the anatomy and morphology from Jabon plant. The purpose of this researchis to know the structures of anatomies roots, steem, and white jabon (A. cadamba) leaves that under go the dry problem (KL 25%) and the water overflow (KL 150%). This research started on August to December 2014. Making of organs preparat place is used the paraffin method. The dry tense is caused the measurement of pori xylem cell to cross slicing of roots and steem of white jabon become smaller, beside that the tense of dry is also caused the measurement of cells mesofil tissues to the leaves organs is more smaller with the broken cells. The water overflows tense is caused the cells to korteks tissue roots and steem of white jabon is not become regular and under go the thicking cell layer, and it can not differenciated limit between second layer palisade with spons tissues.